PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERMUATAN KECERDASAN KOMPREHENSIF BERBASIS MODEL PBL PADA PEMBELAJARAN FISIKA KELAS X TINGAT SMA - Alfira, Ade; ', Rahmad; ', Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this research was to produce student worksheet with comprehensive intelligence based on PBL model’s on learning physics class X in SHS was valid. This research type using Research & Development (R & D). The subject of this research was teaching materials in the form of student worksheet 1, student worksheet 2 and student worksheet 3 validated by validator consisting of 3 lecturers of Physics Education FKIP Universitas Riau and 2 physics teachers. Data analysis technique used in this research was descriptive analysis conducted by calculating from the average value of assessment on validation assessment instrument by validator. The results obtained by student worksheet valid after 2 validation because there are still indicators that are still categorized low. After validation-2 obtained a valid student worksheet with average validity of each LKPD is 3.27 with Very High category for student worksheet 1, 3,26 with Very High category for student worksheet 2 and 3.25 with Very High category for student worksheet 3. This indicates that student worksheet is valid and feasible to be used as one of the teaching materials that can improve students' competence in class X SHS.Keyword: Student Worksheet, Comprehensive Intelligence, PBL Model’s